Mechanism Kinematics Analysis of Two-leg Shield Hydraulic Support - Wang Hongwei; Dong Zhifeng (Jixie chuandong)
As a multi-linkage mechanism with multi-degree of freedom,the two-leg shield hydraulic support is comprised of beams,fore and rear links and hydraulic cylinders.It can realize supporting roof,protecting coal wall and moving forward under the function of hydraulic power,and plays an important role in coal mining.According to structure and operating characteristics of the two-leg shield hydraulic support,the geometrical relationship and calculations about rear link angle and shield beam angle for the supporting height,head distance,leg length and balance cylinder length are deduced.The differential equation of motion for the hydraulic support is established by the Lagrangian theory,and the support type of ZY17300/32/70 is calculated and analyzed.The relationship between angle displacement and velocity for the rear link angle and shield beam angle along with the motion characteristic of supporting height is obtained.The response characteristics of motion velocity and acceleration for top beam are discussed during the working process of lifting up and down.